Study on the evolution process of drying-wetting cycle cracks in compacted loess based on DIC technology - Hu Changming; Hu Tingting; Yuan Yili; Wang Fangfang; Tian Minghui; Hou Xuhui (E3S Web of Conferences, 2023)
Loess cracks and expands easily under the condition of drying-wetting cycles, which will seriously affect the mechanical properties of loess in geotechnical engineering applications and lead to a large number of engineering accidents. Taking the loess in Yan ’an area as the research object, the drying-wetting cycles crack experimental of compacted loess was carried out by a self-made device. The surface crack of loess samples was quantitatively analyzed by using the PCAS system, and the relationship between the surface displacement, strain, and crack evolution during the drying-wetting cycles was analyzed by the digital correlation method (DIC). The results show that loess surface crack development can be divided into three stages: slow growth stage, rapid growth stage, and sluggish development stage. The displacement and strain distribution of loess surfaces are different at different positions, and the development degree of surface cracks varies with the number of drying-wetting cycles. DIC technology can be used for rapid and nondestructive detection of the displacement field and strain field on the surface of loess samples, and dynamic display of the temporal and spatial evolution characteristics of the generation and evolution of loess cracks.